2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6945199
|View full text |Cite
|
Sign up to set email alerts
|

High-density optrodes for multi-scale electrophysiology and optogenetic stimulation

Abstract: We demonstrate the design and implementation of hybrid optical-electrical probes (`optrodes') for high resolution electrophysiology and optogenetic stimulation of neurons in multiple brain areas. Our 64-channel implantable optrodes are minimally invasive (50 μm × 20 μm) and span 1~2 mm. To minimize tethering forces on the brain tissue a monolithic high-density flexible cable (6 μm thin) connects the probe to a lightweight headstage (1.3 gr, 256 channel configuration) designed for awake, freely-behaving small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The demand for a multi-scale, mechanistic comprehension of brain function that accounts for local and whole-brain circuits remains a challenging task. One of the primary hurdles is the need for suitable tools to perform high-resolution monitoring of local neuron ensembles concurrently in various brain regions in awake and freely moving animals (Chamanzar et al, 2014). Given the crescent evidence that numerous cognitive behaviors implicate neural circuits spanned across multiple brain regions, the adoption of distributed recording and stimulation instruments is of utmost importance.…”
Section: Multimodal Neural Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for a multi-scale, mechanistic comprehension of brain function that accounts for local and whole-brain circuits remains a challenging task. One of the primary hurdles is the need for suitable tools to perform high-resolution monitoring of local neuron ensembles concurrently in various brain regions in awake and freely moving animals (Chamanzar et al, 2014). Given the crescent evidence that numerous cognitive behaviors implicate neural circuits spanned across multiple brain regions, the adoption of distributed recording and stimulation instruments is of utmost importance.…”
Section: Multimodal Neural Interfacesmentioning
confidence: 99%
“…For such requirements, the use of micro and nanofabrication techniques is becoming a popular approach, providing new opportunities to produce compact, integrated and scalable optoelectronic probes. An example of microfabricated optrodes for high resolution electrophysiology and optogenetic stimulation is provided in Chamanzar et al (2014). The authors describe the design and implementation of minimally invasive (50 μm × 20 μm) implantable optrodes with a siliconparylene electrical layer for extracellular recording and an Technologies for optogenetic stimulation.…”
Section: Multimodal Neural Interfacesmentioning
confidence: 99%
“…Sometimes high-density collection is needed to ensure the measurement accuracy. M. Chamanzar et al [ 46 ] have demonstrated a scalable process for fabricating compact, high-density optrodes for electrophysiology recording and optical stimulation in multiple brain areas. The headstage stack is assembled and fixed to the skull and each probe is independently implanted into the cortex using a robot-assisted stereotaxic micromanipulator (Neurostar, Germany) equipped with piezo-actuated micro-tweezers (Smarac, Germany) ( Figure 2 a), which allows probes to be inserted into the brain without exerting lateral force that may damage the brain tissue.…”
Section: Bioelectric Signal Monitoringmentioning
confidence: 99%
“… Implantable flexible sensors: ( a ) four independent probes implanted into the mouse visual cortex [ 46 ] © 2014 IEEE; ( b ) flexible SiC-on-PI devices wrapped around a curved surface (diameter = 12 mm) [ 48 ]; ( c ) the electrode sample prepared in this work. Dimensions (L = 5 cm, W = 0.6 cm and t = 0.2 cm) [ 21 ] © 2018 IEEE; photos of implants used in ( d ) biocompatibility tests; ( e ) photos of implants used in biocompatibility tests; ( f ) polydimethylsiloxane (PDMS) encapsulated and ( g ) non encapsulated electrodes [ 22 ].…”
Section: Figurementioning
confidence: 99%
“…These factors can plague both electrical and optical methods of recording and stimulation. Various methods have been explored to manage these factors, by both miniaturizing (Szarowski et al, 2003; Seymour and Kipke, 2007; Kozai et al, 2012) and altering compliance of implanted neuroprosthetics (Szarowski et al, 2003; Seymour and Kipke, 2007; Ware et al, 2012; Chamanzar et al, 2014; Sohal et al, 2016). Reducing the size of elements in prosthetics automatically increases mechanical compliance due to the fourth order scaling of compliance with reductions in cylinder radius.…”
Section: Introductionmentioning
confidence: 99%